Internal Operating Environment, Forecasting Techniques and Accuracy of Performance Forecasting - Chindia, E W (Advances in Social Sciences Research Journal, 2017)
This article examines the influence of the internal operating environment (IOE) on the accuracy of performance forecasting (APF) in large manufacturing firms (LMFs) in Kenya. The objective of this project was to assess if any aspects of the IOE influenced measures of APF. APF, in manufacturing operations, is seldom derived accurately due to internal conflicts of interest. However, since LMFs hire skilled personnel, this study assumes that the qualified forecasting staff ensures accuracy in forecasts when preparing future budgets. IOE is said to influence the behavior of operations resulting in either adverse or favorable organizational performance. This study identified IOE factors that impact firm performance and tested these against measures of APF. Regression analysis was applied using data collected through a structured questionnaire administered among randomly selected LMFs. Results indicated that there was no evidence that IOE had an influence on APF, but it had a moderating effect on the relationship between the objective forecasting technique and APF through return on sales (ROS).